Penerapan Media Gambar Dengan Teknik Kolase dalam Mengembangkan Keterampilan Motorik Halus dan Pembentukan Karakter Anak Usia 5-6 Tahun di TK PGRI Cigugur - Novi Yanti Ulpah; Tati Kartini; Erniawati Erniawati; Lilis Saidah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
One of the activities that can develop fine motor skills in early childhood is to use collage technique picture media. Apart from developing fine motor skills, collage techniques can also be used to build children's character. The purpose of this study is: To find out how teachers apply picture media with collage techniques to improve fine motor skills and shape children's character. The type of research used is a qualitative-descriptive model approach, namely an approach that seeks to describe a symptom, an event that occurs. The methods used are observation, interviews and documentation. The results of the research conducted at PGRI Cigugur Kindergarten, concluded that: Teachers at PGRI Cigugur Kindergarten apply types of image media with collage techniques in developing fine motor skills and forming children's character quite well. So that children have the ability to move one hand, scribble, write, cut, fold and paste. As in character building, children are trained to be patient, conscientious, confident, creative, able to solve problems and be responsible